Factors Affecting the Accuracy of Performance Indicators Deviation Page III DIPA in Level 1 Work Units at the Ministry of Foreign Affairs - Raden Aris Hermawan; Achmad Lutfi (Green Publisher Indonesia, 2024)
This research aims to analyze the factors influencing the Deviation Indicator Page III of the Budget Implementation Document (DIPA) policy by using the Budget Implementation Performance Indicator (IKPA) at Level 1 Work Units of the Ministry of Foreign Affairs. The implementation of IKPA is expected to encourage improvements in financial management accountability through increased compliance of Ministry/Agency Work Units with budget implementation regulations. The research locus is the Level 1 Work Units of the Ministry of Foreign Affairs during the 2023 period. The research data is sourced from secondary data. The results of the research indicate that staff mutations, competency, and leadership commitment influence the accuracy of the Budget Realization Report (RPD) as measured through the Deviation Indicator Page III of DIPA.